2013
DOI: 10.1111/1440-1681.12136
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial caveolar subcellular domain regulation of endothelial nitric oxide synthase

Abstract: SUMMARY Complex regulatory processes alter the activity of endothelial nitric oxide synthase (eNOS) leading to nitric oxide (NO) production by endothelial cells under various physiological states. These complex processes require specific sub-cellular eNOS partitioning between plasma membrane caveolar domains and non-caveolar compartments.eNOS translocation from the plasma membrane to intracellular compartments is important for eNOS activation and subsequent NO biosynthesis. We present data reviewing and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 94 publications
(111 reference statements)
4
41
0
Order By: Relevance
“…Consistent with previous reports [17, 18, 98, 99, 118120 ], we have recently shown that uterine artery endothelium (UAendo) total eNOS was elevated during the follicular phase and pregnancy [6]. The reported stimulatory phosphorylation site serine 635 (S635), an index of enzyme activity in UAendo [121, 122 ], was also elevated by pregnancy suggesting that both expression capacity and activity of eNOS are increased to accommodate increases in UBF. Additionally, we reported a pregnancy-associated adaptation in nonreproduc-tive OAendo which showed increases in both P 635 eNOS and total eNOS [6], the latter confirming our previous observation [18].…”
Section: Pregnancy-induced Changes In Cell-signalingsupporting
confidence: 85%
“…Consistent with previous reports [17, 18, 98, 99, 118120 ], we have recently shown that uterine artery endothelium (UAendo) total eNOS was elevated during the follicular phase and pregnancy [6]. The reported stimulatory phosphorylation site serine 635 (S635), an index of enzyme activity in UAendo [121, 122 ], was also elevated by pregnancy suggesting that both expression capacity and activity of eNOS are increased to accommodate increases in UBF. Additionally, we reported a pregnancy-associated adaptation in nonreproduc-tive OAendo which showed increases in both P 635 eNOS and total eNOS [6], the latter confirming our previous observation [18].…”
Section: Pregnancy-induced Changes In Cell-signalingsupporting
confidence: 85%
“…These results suggest that a defect in EC is responsible for decreased NO bioavailability. In blood vessels, NO is produced by endothelial NO synthase (eNOS), the activity of which is regulated by Ca 2+ /calmodulin, binding of regulatory cofactors and posttranslational modifications including phosphorylation of Ser1177 which sensitizes eNOS to Ca 2 + , stimulating NO production 3638 . To determine whether decreased eNOS activity is responsible for decreased NO production in Rap1b-deficient ECs, we examined agonist-induced phosphorylation of eNOS at Ser1177 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of NO is regulated by eNOS activation in the heart [45]. The agonistinduced dephosphorylation of eNOS-Thr 495 in the calmodulin-binding domain is entirely Ca 2+ -dependent [42,46].…”
Section: The Effects Of Agiv On the Pi3k/akt/enos Signaling Pathwaymentioning
confidence: 99%